2022
DOI: 10.3389/fnagi.2022.836311
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Effects of IL-1β and IL-18 on the Association Between Vitamin D Levels and Mild Cognitive Impairment Among Chinese Older Adults: A Case–Control Study in Taiyuan, China

Abstract: ObjectiveMild cognitive impairment (MCI) is a common, chronic, and complex disease in the elderly, which is often influenced by a variety of factors that include nutrition and inflammation. This study was undertaken to evaluate the mediation effects of inflammation on the association between vitamin D levels and MCI.MethodsWe explored the associations of inflammation and cognitive impairment related to 25(OH)D3 deficiency among 360 older people from the communities in China. Demographic characteristics, lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Our findings were in line with existing evidence on the positive association between peripheral levels of IL-18 and neurocognitive deficits in older adults with MCI ( Cheng et al, 2022 ) and patients with AD ( Bossù et al, 2008 ; Chen et al, 2014 ; Swardfager et al, 2010 ) and further extended it in healthy individuals. IL-18 participates in regulating several immune pathways including inflammasome activation and the development of Th1, Th2 and Th17 responses ( Harel et al, 2022 ; Sharma and Kanneganti, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings were in line with existing evidence on the positive association between peripheral levels of IL-18 and neurocognitive deficits in older adults with MCI ( Cheng et al, 2022 ) and patients with AD ( Bossù et al, 2008 ; Chen et al, 2014 ; Swardfager et al, 2010 ) and further extended it in healthy individuals. IL-18 participates in regulating several immune pathways including inflammasome activation and the development of Th1, Th2 and Th17 responses ( Harel et al, 2022 ; Sharma and Kanneganti, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Systemic inflammation induces neuroinflammation, together with blood-brain barrier breakdown and neuropathological protein aggregation provokes neurodegenerative changes ( Galea, 2021 ; Hoogland et al, 2015 ; Kempuraj et al, 2016 ; Perry, 2010 ). Elevated peripheral inflammatory markers (i.e., interleukin [IL]-6, IL-18 and tumour necrosis factor [TNF]-α) and a higher level of neuroinflammation have been detected in people suffering from Alzheimer's disease (AD) and mild cognitive impairment (MCI) ( Bradburn et al, 2019 ; Cheng et al, 2022 ; Darweesh et al, 2018 ; Leonardo and Fregni, 2023 ; Shen et al, 2019 ). Particularly, the T helper (Th) 1 response plays a particularly important role in maintaining systemic inflammation, which is further associated with neurocognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 have been shown to be a diagnostic marker and predictor of inflammatory conditions like myocardial ischemia ( 106 ), acute respiratory distress syndrome ( 107 , 108 ), chronic obstructive pulmonary disease ( 109 ), post infectious bronchiolitis obliterans ( 110 ) and sepsis-induced multi organ injury ( 111 ). IL-18 has also received increase attention in the pathophysiology of neuro-vascular diseases such as in intracerebral hemorrhage ( 112 ), Japanese encephalitis ( 113 ), ocular Behcet disease ( 114 ), abdominal aortic aneurysm ( 115 ), amyotrophic lateral sclerosis ( 116 ), glioma ( 117 ) and most interestingly in cognitive impairment ( 118 ) and agitation in severe mental disease ( 119 ).…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…However, when there is an exacerbated accumulation of Aβ, the microglia suffer a functional deterioration that facilitates neurotoxicity [ 85 , 86 ]. Specifically in Alzheimer’s disease, it has been shown that in addition to plaques and neurofibrillary tangles, chronic neuroinflammation is the third main pathological feature of Alzheimer’s disease, and is generated by the activation of microglia cells and the release of cytokines [ 87 ] such as TNF-α, a proinflammatory cytokine, which is elevated in patients with Alzheimer’s disease [ 88 , 89 ] as well as IL-6, IL-12, and IL-18, IFN-γ, chemokine (MCP-1), and other neurotoxic agents [ 90 , 91 ]. Another characteristic observed with AD is that the percentage of Treg cells and the levels of TGF-β in the blood of patients with mild cognitive impairment is higher in relation to patients with dementia.…”
Section: Degenerative Diseases and Treg Cellsmentioning
confidence: 99%